The acclimatization strategies of kidney vetch (Anthyllis vulneraria L.) to Pb toxicity - Piwowarczyk, Barbara; Tokarz, Krzysztof; Muszyńska, Ewa; Makowski, Wojciech; Jędrzejczyk, Roman; Gajewski, Zbigniew; Hanus-Fajerska, Ewa (Environmental science and pollution research international, 2018)
Kidney vetch ( Anthyllis vulneraria L.) is a well-known Zn hyperaccumulator. Zn often occurs with Pb in one ore; thus, plants inhabiting waste dumps are exposed not only to Zn but also to Pb toxicity. While the response of kidney vetch to Zn toxicity is relatively well known, the Pb survival strategy of Anthyllis vulneraria has not been the subject of investigations. The aim of presented research was to determine the survival strategy of kidney vetch exposed to high lead concentrations. Shoot explants of a calamine kidney vetch ecotype were placed on agar media containing 0.0, 0.5, 1.0, and 1.5 mM Pb. Morphological, physiological, and biochemical responses, in particular photosynthetic apparatus of plantlets, were examined. The most pronounced changes were observed in plants grown on media supplemented with 1.5 mM Pb after 8 weeks of culture. Increased dry weight and high lead accumulation were observed in roots. Similarly, in shoots, increased dry weight and a decreased number of newly formed shoots were recorded. The accumulation of lead was many times lower in shoots than in roots. In leaf cells’ ultra-structure, looser arrangement of chloroplast thylakoid grana was observed. Despite the decrease in chlorophyll a and carotenoid content, the photosynthetic apparatus remained efficient due to the lack of photoinhibition and increased electron transport rate beyond photosystem II (PSII). For the first time, an acclimatization mechanism based on maintaining the high efficiency of photosynthetic apparatus resulting from increasing of electron transport rate was described.